200 skills every cook must have : the step-by-step methods that will turn a good cook into a great cook - Paul, Clara; Treuille, Eric (Richmond Hill, Ontario : Firefly Books, 2013)
"'200 skills every cook must have'" is an illustrated guide to the most important tips and techniques that are the key to cooking with confidence and consistency. The book explains and illustrates every important technique, from impressive knife skills to
Essential equipment -- Sauce skills -- Vegetable skills -- Fruit and nut skills -- Meat skills -- Poultry skills -- Seafood skills -- Egg skills -- Pastry and baking skills -- Pasta, grain, legume and bread skills -- Broth skills -- Spice skills -- Glossary of ingredients -- Dictionary of terms -- Resources -- Conversion charts.
Includes index.
Keywords: Cooking; Cooking; Cookbooks